Is unconditional basic income a viable alternative to other social welfare measures? - Ugo Colombino (IZA World of Labor, 2015)
Automation and globalization have brought about a tremendous increase in productivity, but also accelerated job destruction, systemic risks, and greater income inequality. Current social policies may not be adequate for achieving the goals of redistributing the gains from automation and globalization, providing efficient buffers against economic shocks, and advancing the reallocation of jobs and skills. Under certain circumstances, an unconditional basic income might be a better alternative for achieving those goals. It is simple, transparent, and has low administrative costs, though it may require higher taxes.
Keywords: I38; H24; 330; basic income; means testing; incentives; redistribution; globalization; automation